Venturing into the digital economy: an examination of an electronic business corporate entrepreneurship team - Lewis, Jeffrey S., author; Geroy, Gary D., advisor; Daly, Joseph, committee member; Edgeman, Rick, committee member; Hartman, Jackie, committee member (Colorado State University. Libraries, 2000)
We now have a business environment enhanced by digital technology. One of the keys to success in the digital economy is the appropriate management of human capital. Because of the sweeping changes being initiated by technology, some human capital management behaviors may not be suitable for the new digital domain. Traditional businesses will need to evolve and transition into the New World of electronic business. The study implements qualitative case study methodology to examine an electronic business corporate entrepreneurship team within a traditional business. The study was designed to identify human resource development related factors emerging from the digital economy. Additionally, the study endeavored to discover hypotheses related to the impact of the factors on traditional businesses. To that end, twelve hypotheses are proposed in the discussion section of this dissertation. The notion that digital economy factors do impact corporate entrepreneurship teams within traditional businesses is supported by this study. The study also supports the claim that human capital must be managed and deployed uniquely when interacting with digital economy factors.
Keywords: studies; research; collaboration; success; communication; values; television sets; interviews; innovations; computers; teams; personal computers; power; knowledge; copyright